(untitled) (Research, Society and Development, 2022)
Probabilistic data have shown in recent decades a growth in dissatisfaction with the personal image of individuals, including in Brazil, which has already become the 4th country in the world ranking in the aesthetics market. Given this reality, this study aimed to discuss the role of the pharmaceutical professional in aesthetic health and to present the regulations of the aesthetic pharmacist. Thus, the current legislation, the services provided and the influence of the work of the Pharmacy professional in the field of aesthetics were presented. This is a literature review carried out based on research of scientific articles, legislation and resolutions, already published in Portuguese and English and that deal specifically with the proposed theme. Data collection took place in a database, such as the Virtual Health Library (VHL), Lilacs, Scielo, PubMed, and Google Scholar. The search resulted in 40 articles after using the inclusion and exclusion criteria; 21 articles remained for analysis, interpretation and discussion. In the results, it was evident that in addition to the area of action of the pharmacist in the area of aesthetics is wide, being able to perform, among others, the techniques of electrotherapy, intense pulsed light, cosmetotherapy, chemical and mechanical peeling, and mainly in the evaluation, definition of the procedures and strategies, monitoring and aesthetic evolution. In addition, the aesthetic pharmacist can be the technician in charge of establishments for aesthetic purposes with non-surgical invasive procedures.